Bad manners on the creative potentials of modifying other artists' work - Chapman, Jake 1966-; Etgar, Yuval (Ridinghouse, 2022)
Bad Manners is an original history of non-consensual collaboration between artists, from the first decades of the twentieth century to the present day. Narrated by artist Jake Chapman and art historian Yuval Etgar, this book takes the reader through a wealth of artworks and anecdotes involving cannibalistic acts of modification or alteration of another artist's work, the hijacking of authorship through the addition of a signature, and occasions when the identities of artists or their creations are cast in doubt. Among the works in discussion are a drawing by Pablo Picasso signed as Henri Matisse, a coffee table executed by Martin Kippenberger using a painting by Gerhard Richter as its surface, and a performance by David Hammons documenting the artist urinating on a Richard Serra sculpture.0Published to accompany an exhibition of the same name at Luxembourg + Co., London, Bad Manners raises questions concerning the nature of artistic authorship, standards of collegial etiquette, plagiarism and ownership. Exhibition: Luxembourg + Co., London, UK (01.03.-15.05.2022)
Keywords: Geschichte 1900-2020; Plagiat; Rezeption; Künstler; Änderung; Geistiges Eigentum; Kunstwerk; Luxembourg + Co. (Gallery) / Exhibitions; Artistic collaboration / Exhibitions; Art / Adaptations / Exhibitions; Art / Corrupt practices / Exhibitions; Art; Adaptations; Artistic collaboration; Exhibition catalogs; Ausstellungskatalog -- Luxembourg + Co -- 01.03.2022-15.05.2022 -- London